Psychological need satisfaction, intrinsic motivation and affective response to exercise in adolescents - Schneider, Margaret L. (2013)
OBJECTIVES: To further understanding of the factors influencing adolescents’ motivations for physical activity, the relationship of variables derived from Self-Determination Theory to adolescents’ affective response to exercise was examined. DESIGN: Correlational. METHOD: Adolescents (N = 182) self-reported psychological needs satisfaction (perceived competence, relatedness, and autonomy) and intrinsic motivation related to exercise. In two clinic visits, adolescents reported their affect before, during, and after a moderate-intensity and a hard-intensity exercise task. RESULTS: Affective response to exercise and psychological needs satisfaction independently contributed to the prediction of intrinsic motivation in hierarchical linear regression models. The association between affective response to exercise and intrinsic motivation was partially mediated by psychological needs satisfaction. CONCLUSIONS: Intrinsic motivation for exercise among adolescents may be enhanced when the environment supports perceived competence, relatedness, and autonomy, and when adolescents participate in activities that they find enjoyable.